Curcuminoids: Implication for inflammation and oxidative stress in cardiovascular diseases. (4th March 2019) - Li, Cheng; Miao, Xiao; Li, Fengsheng; Adhikari, Binay Kumar; Liu, Yucheng; Sun, Jian; Zhang, Rong; Cai, Lu; Liu, Quan; Wang, Yonggang
Abstract : It has been extensively verified that inflammation and oxidative stress play important roles in the pathogenesis of cardiovascular diseases (CVDs). Curcuminoids, from the plant Curcuma longa, have three major active ingredients, which include curcumin (curcumin I), demethoxycurcumin, and bisdemethoxycurcumin. Curcuminoids have been used in traditional medicine for CVDs' management and other comorbidities for centuries. Numerous studies had delineated their anti‐inflammatory, antioxidative, and other medicinally relevant properties. Animal experiments and clinical trials have also demonstrated that turmeric and curcuminoids can effectively reduce atherosclerosis, cardiac hypertrophy, hypertension, ischemia/reperfusion injury, and diabetic cardiovascular complications. In this review, we introduce and summarize curcuminoids' molecular and biological significance, while focusing on their mechanistic anti‐inflammatory/antioxidative involvements in CVDs and preventive effects against CVDs, and, finally, discuss relevant clinical applications.